The Legal Consequences of Debtor Transfer Carried out under the Agreement, House Ownership Loans - Putu Ayu Sriasih Wesna; Ida Bagus Dwi Jusarata; Johannes Ibrahim Kosasih (Jurnal Hukum Prasada, 2022)
Mortgage agreements often find cases, including the transfer of rights to the mortgage object, namely the house, which is carried out under the hands of the debtor to another party before the mortgage is paid off without the knowledge of the bank. This research aims to examine the validity of the house sale and purchase agreement on house ownership loans (KPR), through the debtor transfer process and to examine the legal consequences of the transfer of debtors carried out under the hands of a mortgage agreement, and also to examine the efforts have been taken by the bank to overcome it. This research used normative legal research. The results of this research showed that the transfer of debtors in general can occur with the knowledge of the bank and without the knowledge of the bank (under the hands). It can be concluded that the debtor transfer process is a form of sale and purchase agreement made between the old debtor, who is still bound by the bank credit agreement, and the new debtor. The process of transferring debtors legally must be carried out between three parties, namely the bank, the old debtor and the new debtor. The debtor transfer process must meet the requirements for a valid credit agreement, which is based on Article 1320 of the Civil Code. If there is a transfer of the debtor without the knowledge of the bank, legal remedies must be taken by the new debtor by filing a lawsuit against the old debtor and the bank to the District Court. This decision from the District Court which has permanent legal force (inkracht) is evidence of the existence of an agreement between the old debtor and the new debtor, and can be the basis for the bank to submit certificates and other documents to the new debtor. In order to avoid problems in the future, people who want to transfer debtors to mortgages can do so after obtaining approval from the bank as creditor.